Microstrip Antenna with a Defective Ground Structure (DGS) Motor for Wireless Fidelity Applications (Wi-Fi) at 2.4 GHz - Azizah Firdausa; Nasrul Nawi; Uzma Septima (Politeknik Negeri Padang, 2024)
Wireless fidelity (WiFi) is a wireless connection using radio technology so that users can transfer data quickly and safely. However, at a certain distance there is a decrease in signal speed on WiFi, as happened in Tursina's rented house located in Pasar Baru. When away from WiFi, the internet speed will decrease and the connection becomes unstable. Therefore, an antenna that has a high gain is needed in the form of a microstrip antenna with a working frequency of 2.4 GHz. This final project aims to design a microstrip antenna with the Defected Ground Structure (DGS) method for wireless fidelity (WiFi) applications at a frequency of 2.4 GHz, and analyse antenna parameters such as return loss, VSWR, bandwidth, gain, and radiation pattern. Where the antenna design uses CST Studio Suite 2019 software. After the simulation results are as desired, then fabrication or manufacture of the antenna is carried out. The simulation results after optimising are return loss -40.79 dB, VSWR 1.019, bandwidth 543.9 MHz, gain of 1.312 dBi and bidirectional radiation pattern. After the simulation is carried out, the next fabrication or manufacture of the antenna. In the measurement of the fabricated microstrip antenna using Vector Network Analyser shows a return loss value of -16.07 dB and VSWR 1.375. the measurement results of the fabricated antenna meet the specifications of a good antenna for WiFi applications.